Development of current control for three phase multilevel inverter - Zolkeplee, Muhammad Qhuzaifah (2014)
Inverter is a device, a type of electronic converter in which purpose is to convert a DC signal to AC signal. This project aims to develop a current control method for a multilevel inverter. The purpose of adding a controller is so that the output from the said device, can be controlled and maintained. The simulations of the project are done by using MATLAB Simulink. Results obtained are from the open loop test and closed loop test. Two stages cascaded H bridge are created in which it uses 12 PWM signals for the switching scheme. PWM signals are generated by comparing a sine wave and triangular wave. Switching frequency for this project is chosen to be at audible range of 20kHz. PI controller is used for this project, in which it is set to control current at value of 0.5A and 0.8A. Current sensor is used for detection, in which it will output current value in terms of voltage. The sensitivity is around 40mV/A and with starting value of 2.5V at 0A. It is used for the measurement of the output current, in which it is processed inside microprocessor board, TI C2000 TMS320F28335 for controlling process. Multilevel system created is tested with RLC load in order to verify the validity of the methods used. The results obtained are very much satisfactory in both test. Multilevel inverter produce twice the voltage supplied, as how it should works theoretically. The waveform shapes obtained are of a staircase, 3 level output. Voltage is supplied at lOV and giving the total output of 20V. Current output comparison shows that the closed loop with control element yield better waveforms than the open loop test.